Tooth loss and depression in the elderly: a literature review (Research, Society and Development, 2022)
Objective: To review publications on the relationship between tooth loss and depression in the elderly. Methodology: This is a literature review carried out in PubMed, LILACS and Scielo databases, using the descriptors: “tooth loss”, “depression” and “elderly”. Works available in full and published in English and Portuguese were included. For those selected, 101 articles were found, which, after reading the abstracts and applying the selection criteria, resulted in six works for analysis. Results: Health care that protects health from cuts also causes low aesthetics and function and can affect mental health. Impairment in speech, speech and aesthetics are pointed out as process intensifiers, the loss of the potential dental factor for the development of depressive disorders. Conclusion: Important adoption of teeth also increases the maintenance of the number of problems prevention, but there is no fight against the signs of depression that can be faced with the reduction of the number of teeth.